Kriteria Alat Bukti Elektronik yang Sah dalam urgensi pembaharuan KUHAP - Febryan Alam Susatyo (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2023)
The background of this journal writing is the absence of clear provisions in the Indonesian Criminal Procedure Code (KUHAP) or other specific laws that comprehensively regulate the criteria for valid electronic evidence. Therefore, a legal reform is needed in Indonesia's national criminal procedure law that is more relevant in addressing the current legal developments. Through legal research methodologies such as the statutory approach, case approach, historical approach, comparative approach, and conceptual approach, the author identifies the importance of reliable, credible, relevant, and material requirements in determining the criteria for valid electronic evidence. Furthermore, the acquisition of such electronic evidence should also adhere to the principles of Exclusionary Rules in order to uphold human rights. Subsequently, the Draft Criminal Procedure Code (RUU KUHAP) has regulated electronic evidence, which was previously not addressed in the previous version of the KUHAP. Thus, the importance of KUHAP reform is to establish a fair and adversarial criminal procedure legal principle.